Application of heavy metals sorbent as reactive component in cementitious composites. (20th October 2018) - Keppert, Martin; Doušová, Barbora; Reiterman, Pavel; Koloušek, David; Záleská, Martina; Černý, Robert
Abstract: Sorption is technologically simple and cost-effective method for removal of heavy metals from waste waters. Wide range of sorbent can be used; aluminosilicates materials (clay minerals, zeolites) are well known for their ability to sorb ionic species from water solutions. Ceramic materials belong to aluminosilicates as well; the present paper deals with utilization of ceramic powder, generated as waste product in production of hollow bricks, as sorbent for heavy metals. Pozzolanic activity – i.e. ability to replace part of cement in concrete – is another attribute of powdered ceramic materials. The red-clay based ceramic powder was primarily used as sorbent for Cu, Pb and Zn. The sorption experiments revealed that application potential of ceramic sorbent is comparable with other aluminosilicate, low-cost sorbents. The sorption capacity decreased in sequence Cu > Pb > Zn (sorption capacity 91, 186 and 43 mg g −1 ). Secondly the sorbent with adsorbed metal species was used as cement replacing addition in concrete. This approach has two relevancies; 1) the substitution of cement by ceramic saves natural resources and concrete carbon footprint and 2) the cementitious matrix provides solidification/stabilization of adsorbed species. The unused ceramic powder was found to be very efficient cement substitute (28-days compressive strength 70 MPa was reached); unfortunately the adsorbed metals species influenced negatively the rate of setting and strengthening of concrete. The significant retardation effect was observed in case of Cu, while the influence of Pb and Zn was highly dependent on the sorbent dosage. The studied ceramic powder has not any commercial application yet, but the achieved experimental results indicate its perspective application as low-cost sorbent of ionic species. Highlights: Waste ceramic powder can be used as efficient sorbent of Cu, Pb and Zn. Waste ceramic powder can substitute 30% of Portland cement in concrete without loss of strength or hardening rate. The adsorbed heavy metals reduce the rate of cement hydration when the ceramic sorbent is used as concrete component.